Genetic and clinical characterization of Niemann-Pick disease type C with homozygous NPC1 gene mutation: insights from whole exome sequencing and advanced neuroimaging of two familial cases - Hajira Karim; Lima Oria; Muhsin Elmas (Journal of Biochemical and Clinical Genetics)
Background: Niemann-Pick disease Type C (NPC) is a rare genetic lipid storage disorder characterized by heterogeneous clinical presentations primarily affecting the neurological and visceral systems. This study aims to elucidate the clinical manifestations, radiological findings, and genetic characteristics of NPC, emphasizing the implications of familial aggregation and consanguinity. Case Presentation: We present two cases from a single family, detailing the clinical progression, radiological findings, and genetic mutations. Case 1 involves a 39-year-old male exhibiting symptoms such as dysarthria, cerebellar ataxia, and progressive neurological decline over eight years. Case 2, a relative aged five, displays similar early-onset neurological symptoms. Both cases demonstrate significant cerebellar atrophy on MRI and share a familial NPC1 gene mutation, suggesting a hereditary pattern influenced by consanguineous relationships. Whole Exome Sequencing identified a pathogenic homozygous mutation in the NPC1 gene, confirming the diagnosis of NPC. This finding underscores the genetic basis of the disease and highlights the role of familial genetics in its pathogenesis. Conclusion: These cases underscore the critical role of genetic testing, particularly whole exome sequencing, in diagnosing NPC, which can often present with diverse clinical symptoms. The familial clustering observed also draws attention to the genetic counseling needs in populations with high rates of consanguinity, emphasizing the importance of community genetic studies to understand and manage such rare disorders. [JBCGenetics 2024; 7(1.000): 056-060]